Negative emotionality, self-regulation behaviors, and the teacher-child relationship in preschool classrooms - Jackson, Hayley, author; Barrett, Karen, advisor; Morgan, George, committee member; Youngblade, Lise, committee member (Colorado State University. Libraries, 2012)
This study examines the relationship between levels of negative emotionality, quality of the teacher-child relationship, and self-regulation behaviors in preschool children ages 2.5-5 years (N= 67). It was expected that children with high levels of negative emotionality who experienced a close teacher-child relationship would have higher levels of self-regulation as compared to children with high negative emotionality who had a teacher-child relationship marked with distance or conflict. Negative emotionality and parentally reported self-regulation were assessed using the Child Behavior Questionnaire, teacher-child relationship was measured using the Student-Teacher Relationship Scale, and self-regulation behavior was observed using the Preschool Self -Regulation Assessment. Results were not supportive of the predicted relations among negative affect, student-teacher relationship, and self-regulation. Implications are discussed.